AgNO3/K2S2O8-Promoted Decarboxylative Oxyphosphorylation of Cinnamic Acids: A Mild Synthesis of β-Ketophosphonates - Verma, Aman; Chaudhary, Gyanendra; Manna, Bappa; Devi, Mahima; Yadav, Vivek Kumar; Prabhakar, Amit; Verma, Deepti (Synthesis, 2026)
This works reports an efficient and general method for synthesizing β-ketophosphonate derivatives using AgNO3 as the catalyst and K2S2O8 as the oxidant under mild conditions (room temperature and open-air atmosphere). The procedure is effective under simple and very convenient conditions with easy isolation and purification of the product. Potassium persulfate (K2S2O8) has emerged as a cost-effective, easily accessible inorganic oxidant. K2S2O8 exhibited a unique utility as the most efficient oxidant due to its greater solubility in organic media. A broad substrate scope and suitable functional group compatibility were observed. Experimental studies show that the reaction undergoes a radical process.
Keywords: β-Ketophosphonates; Decarboxylative oxyphosphorylation; C–P bond formation; AgNO3 catalysis; K2S2O8 oxidant; Radical mechanism; Cinnamic acids; Dialkyl phosphites